BML-111 inhibit H2O2-induced pyroptosis and osteogenic dysfunction of human periodontal ligament fibroblasts by activating the Nrf2/HO-1 pathway - Yao Xu; Yi Chu; Wanrong Yang; Kefei Chu; Sihui Li; Ling Guo (BMC, 2024)
Abstract Background Periodontitis is a common and harmful chronic inflammatory oral disease, characterized by the destruction of periodontal soft and hard tissues. The NLRP3 inflammasome-related pyroptosis and human periodontal ligament fibroblasts (hPDLFs) osteogenic dysfunction are involved in its pathogenesis. Studies have shown that lipoxin A4 is an endogenous anti-inflammatory mediator and BML-111 is a lipoxin A4 analog, which was found to have potent and durable anti-inflammatory effects in inflammatory diseases, but the mechanism remains unclear. The purpose of this study was to investigate whether BML-111 inhibits H2O2-induced dysfunction of hPDLFs, attenuates inflammatory responses, and identifies the underlying mechanisms. Methods The oxidative stress model was established with H2O2, and the cell proliferation activity was measured by CCK-8. ALP staining and alizarin red staining were used to detect the osteogenic differentiation capacity of cells; flow cytometry and ELISA were used to detect cell pyroptosis; we explored the effect of BML-111 on hPDLFs under oxidative stress by analyzing the results of PCR and Western blotting. The Nrf2 inhibitor ML385 was added to further identify the target of BML-111 and clarify its mechanism. Results BML-111 can alleviate the impaired cell proliferation viability induced by H2O2. H2O2 treatment can induce NLRP3 inflammasome-related pyroptosis, impairing the osteogenic differentiation capacity of hPDLFs. BML-111 can effectively alleviate H2O2-induced cellular dysfunction by activating the Nrf2/HO-1 signaling pathway. Conclusion The results of this study confirmed the beneficial effects of BML-111 on H2O2-induced NLRP3 inflammasome-related pyroptosis in hPDLFs, and BML-111 could effectively attenuate the impaired osteogenic differentiation function. This beneficial effect is achieved by activating the Nrf2/HO-1 signaling pathway, therefore, our results suggest that BML-111 is a potential drug for the treatment of periodontitis.